Mass transfer characteristics of a fermentation broth in a reactor - Dursun, G; Özer, A; Elibol, M; Özer, D (Elsevier Sci Ltd, 1999)
Gas holdups, dispersion height, volumetric mass transfer coefficients and k(L)a of water and a yeast fermentation broth were studied in a co-current downflow contacting reactor. k(L)a and gas holdup increased with increasing superficial gas velocity and there was a parallelism between k(L)a and gas holdup. The values of k(L)a gas holdup, and dispersion height measured in the air/fermentation broth system were all lower than those in air/water system. (C) 1999 Published by Elsevier Science Ltd. All rights reserved.
Keywords: mass transfer; CDCR; yeast; holdup; gas dispersion; k(L)a